Filozofia Boga: Część II : Odkrywanie Boga (Katolicki Uniwersytet Lubelski Jana Pawla II Wydzial Filozofii, 2017)
This comprehensive guide covers fundamental issues raised by the philosophy of God (often referred to as natural theology, rational theology or theodicy). It provides an overview of philosophical problems over God's existence and God's nature. Wide-ranging in its approach, this companion is particularly useful in Christian colleges, where the philosophy of God is commonly distinguished as a separate subject in philosophical curriculum. The volume is divided into two parts titled respectively "In quest of God" and "Discovering God". This study is arranged in the following sections: * concepts of God in modern philosophical discussion; * agnosticism, atheism; * relationship between philosophical reflection and religious belief; * existence of God; * nature of God; * God's relationship with the world; * reflections on teaching the philosophy of God.